Potential Production of Bioplastic from Water Hyacinth (Eichornia crassipes) - Apzelia Angel Duruin; Xylthea Faith Lalantacon; Jorge Gabriel Leysa; Rogelio Lucero lll; Ralph Adrian Obena; Alisha Sapal; Merlyn Leysa; Anamarie Valdez; Hassanal Abusama (ASEAN Journal of Science and Engineering, 2022)
The purpose of this research was to determine the potential and capability of water hyacinth (Eichornia crassipes) as bioplastics. The produced bioplastic was naturally biodegradable and can be used for natural conservation without environmental destruction.  The study was experimental using various compositions of water hyacinth, characterized by tensile strength and biodegradability tests to determine the potentiality and capability of water hyacinth as a source of bioplastic. In making the bioplastic, we extracted the water hyacinth and utilized glycerine as a plasticizer, water as the solvent, corn-starch as a thickener, and vinegar. After mixing all materials on a pan, the mixed solution was placed on a stainless surface and dried. After a 3-day curing period, the results showed that different mechanical and decomposition properties were obtained. Based on the results of the study, water hyacinth is one of the suitable materials that can be used to produce a new and sustainable bioplastic material. It is organic and accessible, thus making it a candidate for innovation in the creation of bioplastic. Therefore, we believe that the use of water hyacinth is a potential bioplastic material that is beneficial to the environment and the community.